Case report: Anti-ARHGAP26 autoantibodies in atypical dementia with Lewy bodies - Hansen, Niels; Rentzsch, Kristin; Hirschel, Sina; Wiltfang, Jens; Schott, Björn Hendrik; Bartels, Claudia; Lange, Claudia; Bouter, Caroline (Frontiers in Dementia, 2023)
Background: Dementia with Lewy bodies (DLB) is the second most common neurodegenerative dementia. We report a case of dementia involving anti-Rho-GTPase-activating protein 26 (ARHGAP26) autoantibodies that have never been previously associated with DLB. Methods: We describe the case of a 78-year-old man who underwent cerebrospinal fluid (CSF) analysis, magnetic resonance imaging (MRI), 18F-fluorodesoxyglucose positron emission tomography (FDG-PET) and detailed neuropsychological examination. Results: The patient showed mild dementia syndrome associated with extrapyramidal symptoms. Neuropsychological testing revealed impaired cognitive flexibility, figural memory, and verbal memory. Fluctuating cognitive abilities with deficits in attentional-executive dysfunction and visuoconstruction also developed over time. Brain MRI showed reduced biparietal and cerebellar brain volume with generalized accentuation of the outer CSF spaces. His CSF revealed anti-ARHGAP26 autoantibodies also detectable in serum. In differential complementary imaging diagnosis at 2 years, FDG-PET revealed decreased occupancy of the posterior cingulum and precuneus. Although the FDG-PET, MRI, and clinical findings are potentially consistent with AD, negative amyloid biomarkers in CSF make an AD diagnosis highly unlikely. [(123)I]N-omega-fluoropropyl-2beta-carbomethoxy-3beta-{4-iodophenyl}nortropane ([(123)I]FP-CIT) single photon emission computed tomography (SPECT) showed right-sided predominant, reduced dopamine transporter uptake in the putamen, consistent with a positive indicative biomarker finding typical of DLB. Considering the clinically probable DLB associated with the two core features of parkinsonism and fluctuating cognition with deficits in attention supported by an abundant tracer uptake in the right putamen and lower uptake in the left putamen in 123I-FP-CIT-SPECT as an indicative biomarker, we started an antidementia drug applying a cholinesterase inhibitor. Conclusions: Our report shows that atypical DLB may be associated with anti-ARHGAP26 autoantibodies, although its role and significance in DLB’s pathogenesis is unknown. However, it has to mentioned that it is also possible that antibody-specific synthesis of anti-ARHGAP26 autoantibodies are possible hallmarks of a rare autoimmune disease that may be causing the clinical and laboratory features involving altered dopamine transporter uptake in 123I-FP-CIT-SPECT, dementia, and mild Parkinson symptoms, rather than idiopathic DLB with only two core DLB features and inconsistent cognitive and imaging findings. Further research is needed to investigate the role of these autoantibodies in different dementias, particularly in DLB and mixed DLB-AD types.